Effects of larazotide acetate, a tight junction regulator, on the liver and intestinal damage in acute liver failure in rats - Caliskan, Ali Riza; Gul, Mehmet; Yilmaz, Ismet; Otlu, Baris; Uremis, Nuray; Uremis, Muhammed Mehdi; Harputluoglu, Murat (Sage Publications Ltd, 2021)
Background and Aim The epithelial cells are the strongest determinants of the physical intestinal barrier. Tight junctions (TJs) hold the epithelial cells together and allow for selective paracellular permeability. Larazotide acetate (LA) is a synthetic octapeptide that reduces TJ permeability by blocking zonulin receptors. In this study, we aimed to investigate the effects of LA, a TJ regulator, on the liver and intestinal histology in the model of acute liver failure (ALF) in rats. Materials and Methods The thioacetamide (TAA) group received intraperitoneal (ip) injections of 300 mg/kg TAA for 3 days. The TAA+LA(dw) (drinking water) group received prophylactic 0.01 mg/mL LA orally for 7 days before the first dose of TAA. The LA(dw) group received 0.01 mg/mL LA orally. The TAA + LA(g) (gavage) group received prophylactic 0.01 mg/mL LA via oral gavage for 7 days before the first dose of TAA. The LA(g) group received 0.01 mg/mL LA via oral gavage. While liver tissue was evaluated only with light microscopy, intestinal samples were examined with light and electron microscopy. Results Serum ammonia, AST, and ALT levels in the TAA group were significantly higher than in control groups (all p < 0.01). Serum ALT levels in the TAA + LA(dw) group were significantly lower than in the TAA group (p < 0.05). However, serum ammonia and ALT levels did not differ between the TAA and other groups. Serious liver damage in the TAA group was accompanied by marked intestinal damage. There was no significant difference between the TAA and TAA + LA(dw) groups and TAA and TAA + LA(g) groups for liver damage scores. However, intestinal damage scores significantly decreased in the TAA + LA(dw) group compared to the TAA group. In the TAA + LA(dw) group, fusion occurred between the surface epithelial cells of neighboring villi and connecting regions formed as epithelial bridges between the villi. Conclusion Our findings suggest that LA reduced intestinal damage by acting on TJs in the TAA-induced ALF model in rats.
Keywords: Larazotide acetate; celiac disease; liver failure; tight junction